2009
DOI: 10.1021/ja909038t
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected CO2 Splitting Reactions To Form CO with N-Heterocyclic Carbenes as Organocatalysts and Aromatic Aldehydes as Oxygen Acceptors

Abstract: The catalytic reduction of carbon dioxide to carbon monoxide under mild conditions using aromatic aldehydes as reductants and NHCs as organocatalysts was developed. This carbon dioxide splitting reaction provides a new method for metal-free carbon dioxide reduction and steps forward in utilizing carbon dioxide as a renewable "green" source under mild conditions. On the other hand, this reaction also shows a new economical way to oxidize aromatic aldehydes under mild conditions with carbon dioxide and could be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
89
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 186 publications
(94 citation statements)
references
References 28 publications
2
89
0
3
Order By: Relevance
“…The catalyst with the strongest electron donation ligand phenanthroline L10 gave the highest yield. It is well known that NHCs can activate CO 2 in various catalytic transformations (5,7). With that, a unique NHC-Cu cocatalyst was designed by using poly-N-heterocyclic carbene (PNHC) as both ligand and catalyst.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The catalyst with the strongest electron donation ligand phenanthroline L10 gave the highest yield. It is well known that NHCs can activate CO 2 in various catalytic transformations (5,7). With that, a unique NHC-Cu cocatalyst was designed by using poly-N-heterocyclic carbene (PNHC) as both ligand and catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…T he chemical fixation and transformation of carbon dioxide (CO 2 ) has attracted much attention in view of environmental, legal, and social issues in the past few decades (1)(2)(3)(4)(5)(6)(7). Carbon dioxide is an attractive C1 building block in organic synthesis because it is an abundant, renewable carbon source and an environmentally friendly chemical reagent (8)(9)(10)(11)(12)(13).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Initially, Zhang and Gu achieved the NHC-mediated catalytic reduction of CO 2 with aromatic aldehydes as oxygen acceptors. 126 The authors proposed that the NHC catalyst reacts with CO 2 , resulting in an imidazolium In 2010 Nair et al reported a similar NHC−mediated oxidation of aromatic aldehydes with CO 2 leading to carboxylic acids. 127 The expected aryl glyoxylic acid product, resulting from trapping of the Breslow intermediate (Scheme 15, centre) with CO 2 , was not observed.…”
Section: Organocatalysed Co 2 Reductionmentioning
confidence: 99%
“…[6] In a creative and interesting application of a frustrated Lewis pair (FLP), Ashley et al demonstrated the reduction of CO 2 to methanol in the presence of a sterically encumbered phosphine and boranes at 140 8C for nine days. [7] Subsequently we showed that a RP/AlX 3 FLP system could be used to effect the reduction of CO 2 to either methanol or CO under ambient conditions.…”
mentioning
confidence: 99%